Estudio ecológico de los pastizales de dehesa en la provincia de Badajoz. Tipificación preliminar de la vegetación empleando el análisis de correspondencias (Pastos, 1977)
42 grasslands of Badajoz and Huelva provinces (Western Spain) were studied recording plant species frequencies with 10 quadrats (20 X 20 cm.) randomly distributed over 2 X 2 m. plots taken under the crown of Quercus rotundifolia trees. Soil samples collected on every plot were analysed for pH, orgainic matter, P, Ca, K and Na. Frequency matrix (80 plant species X 42 plots) was analysed by the method know as "Analyse des Correspondences" (BENZECRI, 1973). The two main components (accounting for about 20 % of the overall variation) sepárate plots into six recognizable groups (grassland types). A preliminary attempc to interpret those groups is made in terms of biotope (soil and substrate) differencies. The two main directions of variation found correspond to an eutrophization gradient (poor acidic versus rich basic soils) and to an erosión gradient (soil erosión versus pedogenesis). Secondary causes of variation are interpreted as due to lithology, climate and management. Further analysis of present data is currently under way.